Perbedaan Karakteristik Fisik Edible Film dari Umbi-umbian yang Dibuat dengan Penambahan Plasticizer - Yulianti, Rahmi; Ginting, Erliana (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Starch is suitable for edible film, although the film produced is brittle. A study on preparation of edible film from starches of four tuber crops with the addition of plasticizers was conducted at the Chemical and Food Technology Laboratory, of the Indonesian Legumes and Tuber Crops Research Institute (ILETRI), Malang, from March to July 2009. The trial was arranged in a randomized complete design with three replications. The first factors were four difference tuber crops (cassava, edible canna, sweet potato, and arrowroot) and the second factors were two kind of plasticizers (glycerol and sorbitol, each at a concentration of 2% v/w starch). Observations were done on chemical and physical properties of the starches as well as physical characteristics of the edible film produced. Results showed that the interactions between starches and plasticizers significantly influenced colour, tensile strength, and elongation of the edible film. However, the effect of plasticizer on thickness of the edible film was not significant. Arrowroot and cassava starches that have the highest whiteness levels produced edible films with the highest brightness values (L*). Edible films from the four tuber crops starches had similar thickness (0.02-0.03 mm). The arrowroot starch added with either sorbitol or glycerol produced edible films with the highest values of tensile strengh and elongation (1.7 N and 2.6%, and 1.5 N and 2.6%, respectively), indicating for good physical performances of edible films. These characters were followed by starch of sweet potato that was treated with sorbitol or glycerol.